Specialist advice for primary care: an evaluation of a gastroenterology email advice service - Fulton, Alice L (Future Hosp J, 2016)
Communication between primary and secondary care physicians is often unreliable and one sided in the form of clinic letters. Alternatively, general practitioners (GPs) may have difficulty contacting an on-call specialist via outdated hospital paging services. At Imperial College Healthcare NHS Trust, a gastroenterology email advice line was set up to promote dialogue and potentially help GPs deal with issues within their practices. The service has been evaluated both objectively through analysis of enquiries and subjectively through a survey of GPs’ views. Analysis showed a very high level of satisfaction among users of the service. There is also good evidence to suggest that the service has helped to streamline patient management and led to the avoidance of some outpatient appointments.